PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES TERHADAP HASIL BELAJAR IPS SISWA KELAS IV SDN 169 PEKANBARU (Studi Eksperimen Kuasi) - Yola winasti; Hendri Marhadi; Guslinda ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The views of students assume IPS is the subject of memorizing, this results in less learning attract students and impressed only pursue the target to complete the course subject. As a result decreased attention and enthusiasm the students who ultimately student learning outcomes also declining. It is necessary for research learning model examples of non examples. This model is also expected to make students critical, because in the process of this model requires students to comment on the displayed image. The impact is expected to occur in students after learning is complete, in addition to students' understanding of the material provided, students are expected to be personally critical of the problems it faces. The main objective of this study was to determine how much influence the teaching model of cooperative learning examples of non examples to the learning outcomes IPS grade IV SDN 169 Pekanbaru. This research was conducted in SDN 169 Pekanbaru in class as a class IVB IVC control and class as a class experiment using the design nonrandomized control group pretest-posttest design. Based on the results of Wilcoxon Signed Rank Test with significance level α = 0.05 pvalue values obtained (Asymp. Sig. 2-tailed) 0.035 < 0.05. The results of this study indicate that the application of cooperative learning model examples of non examples significantly affect the results of social studies compared the use of learning as usual (do not use the type cooperative model examples of non examples). The influence of cooperative learning model examples of non examples of the results of social studies is approximately 77% with very high category.Key Words: cooperative learning model examples of non examples, learning outcomes IPS.